Population pharmacokinetics of empagliflozin, a sodium glucose cotransporter 2 inhibitor, in patients with type 2 diabetes. (13th August 2013) - Riggs, Matthew M.; Staab, Alexander; Seman, Leo; MacGregor, Thomas R.; Bergsma, Timothy T.; Gastonguay, Marc R.; Macha, Sreeraj
Abstract Data from five randomized, placebo‐controlled, multiple oral dose studies of empagliflozin in patients with type 2 diabetes mellitus (T2DM; N = 974; 1–100 mg q.d.; ≤12 weeks) were used to develop a population pharmacokinetic (PK) model for empagliflozin. The model consisted of two‐compartmental disposition, lagged first‐order absorption and first‐order elimination, and incorporated appropriate covariates. Population estimates (interindividual variance, CV%) of oral apparent clearance, central and peripheral volumes of distribution, and inter‐compartmental clearance were 9.87 L/h (26.9%), 3.02 L, 60.4 L (30.8%), and 5.16 L/h, respectively. An imposed allometric weight effect was the most influential PK covariate effect, with a maximum effect on exposure of ±30%, using 2.5th and 97.5th percentiles of observed weights, relative to the median observed weight. Sex and race did not lend additional description to PK variability beyond allometric weight effects, other than ∼25% greater oral absorption rate constant for Asian patients. Age, total protein, and smoking/alcohol history did not affect PK parameters. Predictive check plots were consistent with observed data, implying an adequate description of empagliflozin PKs following multiple dosing in patients with T2DM. The lack of marked covariate effects, including weight, suggests that no exposure‐based dose adjustments were required within the study population and dose range.